(untitled) (Research, Society and Development, 2020)
Fertirrigation has been instrumental in boosting the world’s food supply, since more than 40% of agricultural production is total in areas irrigated with the use of this technique. However, when poorly managed, it is possible to increase the concentration of salts in the soil, besides increasing the probability of losses of nutrients by leaching, especially in sandy soils. Fertigation as performed today, still being able to print water and nutrients in the face of momentary and abrupt elevation of osmotic potential in the volume of soil explored. This is because the concentration of injected fertilizer solution is not a constant habit irrigation system throughout the operation. The objective of this work was to develop a mathematical program for the management of precision fertigation in an injected fertilization solution without a variable irrigation system, over time, besides verifying the reach of vertical processes by the fertigation thus performed. The mathematical model is used to describe a change in your injectable fertilizer solution in an irrigation system nonuniformly. A quantitative fertigation rate, obtained according to the obtained mathematical model, gives a 25% reduction in vertical range and a higher efficiency of fertilizer solution compared to proportional fertirrigation